Effects of Elevated CO2 on a Natural Diatom Community in the Subtropical NE Atlantic - Bach, Lennart T.; Hernández-Hernández, Nauzet; Taucher, Jan; Spisla, Carsten; Sforna, Claudia; Riebesell, Ulf; Arístegui, Javier (Frontiers in Marine Science, 2019)
Diatoms are silicifying phytoplankton contributing about one quarter to primary production on Earth. Ocean acidification (OA) could alter the competitiveness of diatoms relative to other taxa and/or lead to shifts among diatom species. In spring 2016, we set up a plankton community experiment at the coast of Gran Canaria (Canary Islands, Spain) to investigate the response of subtropical diatom assemblages to elevated seawater pCO2. Therefore, natural plankton communities were enclosed for 32 days in in situ mesocosms ( 8 m3 volume) with a pCO2 gradient ranging from 380 to 1140 µatm. Halfway through the study we added nutrients to all mesocosms (N, P, Si) to simulate injections through eddy-induced upwelling which frequently occurs in the region. We found that the total diatom biomass remained unaffected during oligotrophic conditions but was significantly positively affected by high CO2 after nutrient enrichment. The average cell volume and carbon content of the diatom community increased with CO2. CO2 effects on diatom biomass and species composition were weak during oligotrophic conditions but became quite strong above 620 µatm after the nutrient enrichment. We hypothesize that the proliferation of diatoms under high CO2 may have been caused by a fertilization effect on photosynthesis in combination with reduced grazing pressure. Our results suggest that OA in the subtropics may strengthen the competitiveness of (large) diatoms and cause changes in diatom community composition, mostly under conditions when nutrients are injected into oligotrophic systems.